The power of identity and ideology in language learning designer immigrants learning English in Singapore - DeCosta, Peter (Multilingual education, 2016)
This critical ethnographic school-based case study offers insights on the interaction between ideology and the identity development of individual English language learners in Singapore. Illustrated by case studies of the language learning experiences of five Asian immigrant students in an English-medium school in Singapore, the author examines how the immigrant students negotiated a standard English ideology and their discursive positioning over the course of the school year. Specifically, the study traces how the prevailing standard English ideology interacted in highly complex ways with their being positioned as high academic achievers to ultimately influence their learning of English. This potent combination of language ideologies and circulating ideologies created a designer student immigration complex. By framing this situation as a complex, the study problematizes the power of ideologies in shaping the trajectories and identities of language learners.